(untitled) (UNED Research Journal, 2019)
Climate change is a problem of all human kind; however, there is gender inequality in the impacts of climate change, with greater impacts on women. In 2010, the International Union for Conservation of Nature (IUCN) established a methodology for the development of Gender and Climate Change Action Plans (CCGaps) with the aim to promote a comprehensive and multisectoral approach towards climate change. The CCGaps process includes: 1) Information inventory; 2) Leveling the field; 3) Taking all voices into account; 4) Prioritizing; and 5) Implementation/action. To date, this methodology has been used by 20 national governments and in three regional processes. The methodology established by the IUCN to develop the CCGaps represents an innovative way to mainstream gender perspective. It is based on strengthening the capacity of the interest groups to build adequate, non-conventional, concrete, practical and innovative solutions. A CCGaps focuses on key sectors identified by each country and recognizes gender equality as a transformative engine at a national level.